O Acordo de Cotonou e as migrações climáticas - Marante, Margarida Xavier (2019)
This paper develops a study on the issue of climate change and its consequences at a global level, especially on population migration and its approach from the Cotonou Agreement. Starts from the realization that climate change is a current and urgent concern, the consequences of which will affect all countries on the planet in different ways. However, the poorest and developing countries are the most vulnerable. The impact on countries around the world, particularly as a result of natural disasters, droughts, hurricanes and rising sea levels will seriously threaten the quality of life, the territories and even force the displacement of millions of people per year, which in parallel with survival, will be a matter of security. In line with this concern, it is also noted that there is no established legal concept or regime for climate migrants. Within an international perspective, the study focuses on the Cotonou Agreement, a landmark partnership between the European Union and the APC Group, since 2000, which currently covers 28 UE countries and 79 ACP countries, devoted to poverty eradication, cooperation and political dialogue towards sustainable development. Closely examines the 2010 revision to the Agreement, which has formalized the issue of climate change, acknowledged the special vulnerability of developing countries to the climatic consequences and promoted dialogue and cooperation in order to establish strong strategies of prevention and adaptation. It is noted that the Cotonou Agreement has not added any solutions or prospects for cooperation to respond to population flows due to climate factors, that have already occurred and will only increase in the future, leaving the issue of climate migration unregulated. It is analyzed that the term of validity of the aforementioned Agreement is set for February of next year, so the present work sets out some of the solutions that could regulate the matter of climate migrations in the scope of Cotonou, hoping that the errors of the past will teach us soon enough, in time to diminish the tragedies of the future.